Cross-national variation in the subjective wellbeing of youth in low and middle income countries: the role of structural and micro-level factors. (7th February 2020) - Mutumba, Massy; Schulenberg, John
ABSTRACT: Subjective wellbeing (i.e. life satisfaction and happiness) impacts youth's social, economic and political participation. Prior studies have documented cross-national variation in subjective wellbeing of adults but there is a lack of data on the prevalence and correlates of subjective wellbeing among youth in low and middle income countries. This paper utilizes data from an international dataset – Multiple Indicator Cluster Surveys to assess the influence of structural and micro-level factors on the subjective wellbeing of youth (ages 15–24) in 29 countries or regions in Eastern Europe, Latin America, Asia and Africa. We find that within countries, global life satisfaction and happiness are associated with age, education attainment, place of residence, marital status, household wealth and exposure to mass media. Significant interactions between age, gender and education are observed. However, none of the country level development indicators account for cross-national variation in youth's SWB although there is some indication that income inequities between countries may influence youth's SWB. The findings underscore the need for objective measures of subjective wellbeing to understand the conditions in LMICs.